Endoscopic Endonasal Dacryocystorhinostomy Combined with Canaliculus Repair for the Management of Dacryocystitis with Canalicular Obstruction - Yunhai Tu; Zhenbin Qian; Jiao Zhang; Wencan Wu; Tianlin Xiao (Journal of Ophthalmology)
Purpose. The aim of this study is to propose a simple and efficient combination surgery for the management of dacryocystitis with canalicular obstruction. Methods. A retrospective noncomparative case series of dacryocystitis with canalicular obstruction has been studied. Twelve patients with dacryocystitis and canalicular obstruction underwent a conventional endoscopic endonasal dacryocystorhinostomy (EE-DCR) combined with a modified canalicular repair. Postoperative observations included slit lamp, fluorescein dye disappearance test, lacrimal syringing, lacrimal endoscopy, and nasal endoscopy. Results. After 6–18 months of postoperative follow-up, the symptoms of epiphora and mucopurulent discharge disappeared completely in 10 patients, and occasional or intermittent epiphora remained in 2 patients. All of the twelve patients showed an opened intranasal ostium and normal fluorescein dye disappearance test. Patent bicanalicular irrigation was achieved in 9 patients. One patient had a partial and the other two had a complete reobstruction by lacrimal irrigation to their repaired lower canaliculus; however, all of them had a patent lacrimal irrigation to upper canaliculus. The functional success rate for the combination surgery is 83% (10/12), and anatomical success rate is 75% (9/12). Conclusion. EE-DCR combined with modified canalicular repair is a simple and efficient method for the management of dacryocystitis with canalicular obstruction.